Synergistic interaction between pH and NaCl in the limits of germination and outgrowth of Clostridium sporogenes and Group I Clostridium botulinum vegetative cells and spores after heat treatment. (September 2022) - Boix, Emmanuelle; Coroller, Louis; Couvert, Olivier; Planchon, Stella; van Vliet, Arnoud H.M.; Brunt, Jason; Peck, Michael W.; Rasetti-Escargueil, Christine; Lemichez, Emmanuel; Popoff, Michel R.; André, Stéphane
Abstract: Group I Clostridium botulinum and Clostridium sporogenes are physiologically and genetically closely related. Both are widely distributed in the environment and can cause foodborne botulism. In this work, a physiological study was conducted with 37 isolates from spoiled canned food and five referenced strains of C. sporogenes (three isolates) and Group I C. botulinum (two isolates). Growth limits of vegetative cells were established as a function of pH and NaCl concentration in PYG modified medium (PYGm) at 30 °C for 48 days. The heat resistance of the spores was studied for 2 min and 10 min at 102 °C and 110 °C. This physiological study (pH, NaCl growth limits and heat resistance) allowed the selection of 14 isolates of C. sporogenes (twelve isolates) and Group I C. botulinum (two isolates) representative of the diversity found. This panel of 14 selected isolates (11 isolated from spoiled canned food and three reference strains), were whole genome sequenced, but no association of physiological and genetic characteristics could be detected. Finally, we studied the ability of spores to germinate and grow from 5 isolates (four C. sporogenes and one Group I C. botulinum ), under stress conditions generated by pH and NaCl following a low intensity heat treatment. The accumulation of these 3 stresses creates synergies that will strongly reduce the probability of spore growth in pH and salt conditions where they usually proliferate. The effect is progressive as the conditions become drastic: the number of decimal reduction observed increases translating a probability of growth which decreases. This study provides a better understanding of the behaviour of C. sporogenes and Group I C. botulinum isolates and shows how the combination of pH, NaCl and heat treatment can help prevent or minimise foodborne botulism outbreaks. Highlights: Individual isolates of C. sporogenes and C. botulinum grew at pH ≥ 4.5 and NaCl ≤11.5%. No correlation between physiological and genetic characteristics of 42 isolates. pH and NaCl growth limits differed between vegetative cells and spores. Combined low heat treatment, pH 4.9 and NaCl 4% prevented growth.